Quillaja saponin variants with central glycosidic linkage modifications exhibit distinct conformations and adjuvant activities. Issue 3 (15th January 2016) - Walkowicz, William E.; Fernández-Tejada, Alberto; George, Constantine; Corzana, Francisco; Jiménez-Barbero, Jesús; Ragupathi, Govind; Tan, Derek S.; Gin, David Y.
Abstract : A mouse vaccination model and molecular dynamics studies reveal characteristic conformations of active QS-21 variants. Abstract : Immunological adjuvants such as the saponin natural product QS-21 help stimulate the immune response to co-administered antigens and have become increasingly important in the development of prophylactic and therapeutic vaccines. However, clinical use of QS-21 is encumbered by chemical instability, dose-limiting toxicity, and low-yielding purification from the natural source. Previous studies of structure–activity relationships in the four structural domains of QS-21 have led to simplified, chemically stable variants that retain potent adjuvant activity and low toxicity in mouse vaccination models. However, modification of the central glycosyl ester linkage has not yet been explored. Herein, we describe the design, synthesis, immunologic evaluation, and molecular dynamics analysis of a series of novel QS-21 variants with different linker lengths, stereochemistry, and flexibility to investigate the role of this linkage in saponin adjuvant activity and conformation. Despite relatively conservative structural modifications, these variants exhibit striking differences in in vivo adjuvant activity that correlate with specific conformational preferences. These results highlight the junction of the triterpene and linear oligosaccharide domains as playing a critical role in the immunoadjuvant activity of the Quillaja saponins and also suggest a mechanism of action involving interaction with a discrete macromolecular target, in contrast to the non-specific mechanisms of emulsion-based adjuvants.